1997
DOI: 10.1089/dna.1997.16.1041
|View full text |Cite
|
Sign up to set email alerts
|

Varied Expression Patterns of Human H1 Histone Genes in Different Cell Lines

Abstract: Five main type H1 histones have been described in man (H1.1-H1.5) in addition to the testis specific type H1t and the replacement subtype H1 degrees, which is found mainly in highly differentiated cells. We have isolated this whole complement of H1 genes and have studied the expression of the seven human H1 subtype genes in several cell lines. The RNAase protection assay was used to discriminate between the very similar transcripts derived from the seven H1 subtype genes. With the exception of H1.2 and H1.4, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 59 publications
4
42
0
Order By: Relevance
“…For analysis of cell-cycle-dependent promoter elements, aphidicolin was used to block transfected cells at the transition from the G1 phase to the S phase of the cell cycle [19]). After transfection of four cultures with the identical individual luciferase-promotor construct, as described above, cells were blocked with aphidicolin (final concentration 15 µM) for 24 h. After this blocking, two of the four cultures transfected in parallel were released from the S-phase block by replacing the aphidicolin-containing medium, whereas the other two cultures remained under blocking conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For analysis of cell-cycle-dependent promoter elements, aphidicolin was used to block transfected cells at the transition from the G1 phase to the S phase of the cell cycle [19]). After transfection of four cultures with the identical individual luciferase-promotor construct, as described above, cells were blocked with aphidicolin (final concentration 15 µM) for 24 h. After this blocking, two of the four cultures transfected in parallel were released from the S-phase block by replacing the aphidicolin-containing medium, whereas the other two cultures remained under blocking conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Varied patterns of H1 subtype proteins have been documented in different mouse tissues, depending on the state of development or differentiation [17,18]. Similarly, differential expression patterns of the human H1 histone genes have been observed on comparison of mRNA levels in different human cell lines [19]). This differential expression points towards a functional relevance of the individual H1 subtypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the human linker histone subtype H1.4 as a model, as it is highly abundant, widely expressed (Lennox and Cohen 1983;Meergans et al 1997), and the most conserved human linker histone subtype (Supplemental Fig. S1A).…”
Section: H14k34 Is Modified By Acetylationmentioning
confidence: 99%
“…This is not unexpected, as it had been previously reported that in cells in culture and in mammalian tissue, the H1.2 and H1.4 isoforms are more broadly expressed in all cell types, whereas expression of other H1 isoforms are often down-regulated in differentiated cells. 27,28 To determine the phosphorylation status of these human H1 isoforms, the two HPLC fractions were analyzed by electrospray mass spectrometry and the data are summarized in Table 1. The ESI/MS analyses of the first HPLC peak show ions which correspond in mass to the unmodified H1.0 isoform.…”
Section: Characterization Of Histone H1 Isoform Phosphorylation In Humentioning
confidence: 99%